The Influence of Naproxen on Biological Factors in Leukocyte-Rich Platelet-Rich Plasma: A Prospective Comparative Study - Mannava, Sandeep; Whitney, Kaitlyn E.; Kennedy, Mitchell I.; King, Jill; Dornan, Grant J.; Klett, Katarina; Chahla, Jorge; Evans, Thos A.; Huard, Johnny; LaPrade, Robert F. (Arthroscopy, 2019)
To quantify and compare normative catabolic and anabolic factor concentrations in leukocyte-rich platelet-rich plasma (LR-PRP) at various time points, including baseline, 1 week after initiating naproxen use, and after a 1-week washout period. Asymptomatic healthy donors aged between 18 and 70 years were recruited (average age, 36.6 years; range, 25-64 years). Subjects were excluded from the study if they were actively taking any prescribed medications or nonsteroidal anti-inflammatory drugs (NSAIDs) or if they had any of the following at present or previously: blood or immunosuppression disorders, cancer, osteonecrosis, rheumatoid arthritis, avascular necrosis, NSAID intolerance, gastrointestinal or peptic ulcer disease, or kidney dysfunction. The anabolic factors vascular endothelial growth factor, fibroblast growth factor 2, platelet-derived growth factor AB (PDGF-AB), and platelet-derived growth factor AA (PDGF-AA) and the catabolic factors interleukin (IL) 1β, IL-6, IL-8, and tumor necrosis factor α in LR-PRP were measured. Peripheral blood was drawn at 3 time points: baseline, after 1 week of naproxen use, and after a 1-week washout period. The angiogenic factors PDGF-AA (44% decrease in median) and PDGF-AB (47% decrease) significantly declined from baseline (P < .05) after 1 week of naproxen use. There was a significant recovery (P < .05) of PDGF-AA (94% increase) and PDGF-AB (153% increase) levels after the 1-week washout period, with a return to baseline levels. The catabolic factor IL-6 also had a significant decline from baseline (77% decrease in median, P < .05) after 1 week of naproxen use. After a 1-week washout period, the IL-6 level was similar to the baseline level (130% increase, P < .05). Naproxen use diminished several biological factors in LR-PRP; however, a 1-week washout period was sufficient for the recovery of PDGF-AA, PDGF-AB, and IL-6 to return to baseline levels. Tumor necrosis factor α, IL-1β, IL-8, vascular endothelial growth factor, and fibroblast growth factor 2 did not show differences between the 3 time points of data collection. Discontinuing NSAIDs for a minimum of 1 week before LR-PRP treatment may improve certain biological factor levels. Level II, prospective comparative study.